2002
DOI: 10.1128/aac.46.8.2569-2574.2002
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial Activity of the Antiulcer Agent Omeprazole

Abstract: The benzimidazole compound omeprazole, used widely for the treatment of peptic ulcer disease, inhibits the growth of Leishmania donovani, the causative agent of visceral leishmaniasis. Promastigotes cultured at acidic pH and amastigotes within infected macrophages are reduced 90% or more with 150 M omeprazole. Antiparasitic action of the drug is due to its inhibition of the P-type K ؉ ,H ؉ -ATPase on the surface membrane. This enzyme is important for pH homeostasis and the maintenance of proton motive force ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 17 publications
1
24
0
1
Order By: Relevance
“…Therefore, it seemed conceivable that PPI may specifically get to the tumor site, being an additional acidic compartment in cancer patients. We reasoned that any effect of PPI on tumor cells in vitro would be potentiated by the degree of acidity of the surrounding microenvironment, as already shown for its antimicrobial activity (47,48). Indeed, although the doses at which PPI induced cell death in vitro are higher than plasma concentrations reached in humans at standard dosage, we believe that PPI may achieve higher local concentrations at tumor site.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, it seemed conceivable that PPI may specifically get to the tumor site, being an additional acidic compartment in cancer patients. We reasoned that any effect of PPI on tumor cells in vitro would be potentiated by the degree of acidity of the surrounding microenvironment, as already shown for its antimicrobial activity (47,48). Indeed, although the doses at which PPI induced cell death in vitro are higher than plasma concentrations reached in humans at standard dosage, we believe that PPI may achieve higher local concentrations at tumor site.…”
Section: Discussionmentioning
confidence: 97%
“…The results show that only one tested compound, omeprazole, significantly disrupted asymmetric Ci-Pitx expression ( Fig. 2A) (Mukherjee et al, 2001;Jiang et al, 2002;Levin et al, 2002). The specificity of action has made omeprazole a popular clinical treatment for targeting gastric H ϩ K ϩ ATPase activity in the con- …”
Section: Dechorionation Disrupts Asymmetric Gene Expression In Ciona mentioning
confidence: 99%
“…We therefore investigated whether lysosomal enzymes playa role in OM-induced apoptosis. A number of studies have evidenced the lysosomotropic properties of OM and have indicated that following activation by protonation, it can also affect the activity of proton pumps, such as the vacuolar H+-ATPase (5,6,8,49) in part responsible for the internal acid milieu of! ysosomes (9-10).…”
Section: Fl3mentioning
confidence: 99%